Moral adherence enhancement and the case of long-distance space missions - Huttunen Henri; Sivula Oskari (Elsevier, 2025)
The possibility of employing human enhancement interventions to aid in future space missions has been gaining attention lately. These possibilities have included one of the more controversial kinds of enhancements: biomedical moral enhancement. However, the discussion has thus far remained on a rather abstract level. In this paper we further this conversation by looking more closely at what type of interventions with what sort of effects we should expect when we are talking about biomedical moral enhancements. We suggest that a more grounded way to picture moral enhancement, at least in the near term, is to envision a form of cognitive enhancement that also provides some moral benefits by heightening the enhanced person's capability for acting according to their own subjective moral code. While this concept of moral adherence enhancement also has relevance for the moral enhancement discussion more widely, in this paper we apply it specifically in the context of space missions. We argue that there are weighty reasons to consider making biomedical enhancements of the proposed kind a mandatory feature of early-phase long-distance space travel because these missions are high-stakes in nature and take place in an environment where the enhancement could be seen as conferring important advantages while negating many of the traditional arguments weighed against it.